Finite element simulations to evaluate deformation of polyester tubular braided structures. Issue 10 (June 2017) - Ochola, Jerry; Malengier, Benny; Daelemans, Lode; Van Langenhove, Lieva
The use of narrow tubular braided structures for biological tissue support has made it possible to produce highly flexible and robust soft tissue reinforcement structures. These attributes make the braids ideal in supporting ruptured and broken tissues during healing and regeneration. There have been continued efforts to improve the design in order to reinforce tissues while still maintaining their flexibility; this has been undertaken by exploring the deformation behavior of these structures. Mechanical modeling, which provides an in-depth understanding of the deformation mechanism of structures, plays an important role in designing structural changes in tubular braids. This paper reports the results of numerical and experimental investigations into the radial contraction and deformation mode of two types of tubular braided fabrics—single and double braided—subjected to uniaxial tensile loading under quasi-static conditions. Realistic geometrical structures were developed for mechanical modeling of tubular braids in terms of tensile loads, elongation, radial contraction and braid angle. The results indicated that there was a good match between experimental and simulated tensile behavior of the braided structures. It was established that the amount of braided yarns within the structure had the likelihood of influencing the radial contraction and braid angle in the braided structure under uniaxial tensile deformation. The results portrayed that braided structures would undergo large deformations at low loads. It was also established that there would be more structural stability as the yarns increased, evidenced by more loads in the double-braided structure as compared to the single-braided tubular structure.